Nursing care of one case of chemotherapy-associated oral mucositis treated with Chinese herbal gargle combined with moxibustion (中药漱口联合艾灸治疗1例化疗相关性口腔黏膜炎的护理体会) - PAN Yanchun (潘艳春); WANG Jing (王敬) (Association of Integrative Nursing, 2022)
This paper summarizes the nursing experience of a patient with chemotherapy-associated oral mucositis treated with Chinese herbal mouthwash combined with moxibustion. Firstly, risk assessment and grading were performed; then the herbal mouthwash combined with moxibustion treatment was combined with comprehensive nursing interventions such as personalized diet regulation, emotional care, health guidance and continuation care, in order to reduce the patient's ulcer pain, accelerate ulcer healing, improve his quality of life and enhance his treatment compliance. (本文总结中药漱口联合艾灸治疗1例化疗相关性口腔黏膜炎患者的护理体会。首先进行风险评估和分级, 然后在中药漱口联合艾灸治疗的同时, 配合个性化饮食调护、情志护理、健康指导及延续护理等综合护理干预, 以减轻患者溃疡疼痛, 加速溃疡愈合, 改善其生活质量, 提高其治疗的依从性。)